The Legal Implications Due to Default by the Debtor on a Car Loan Agreement with Fiduciary Guarantee - Wieke Dewi Suryandari; Hono Sejati (Law Development Journal, 2023)
The purpose of this study is to determine and analyze: 1) The legal position of the strength of a car loan agreement with a fiduciary guarantee for creditors and debtors at Commerce International Merchant Bankers (CIMB) 2) The juridical implications of default by the debtor on a car loan agreement with a fiduciary guarantee at Commerce International Merchant Bankers (CIMB) . The approach method used in discussing this research problem is a sociological juridical approach. The research specification used is descriptive analytical research. This type of data uses primary and secondary data. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1) The legal position of the strength of the car loan agreement with fiduciary guarantees for creditors and debtors at Commerce International Merchant Bankers (CIMB) is included in the construction of an anonymous agreement (Innominaat), as far as the contents of the agreement have met the legal requirements (1) of the Civil Code which states that an agreement made legally applies as the law that made it, the CIMB Finance consumer financing agreement, 2) The juridical implication due to default by the debtor on a car loan agreement with a fiduciary guarantee at Commerce International Merchant Bankers (CIMB) is that the creditor does not get the fulfillment of his rights that should be obtained by the existence of the agreement. When the debtor defaults, the thing that will be done by the creditor to get the debt repaid is to sell the object that is guaranteed by the debtor. Another legal consequence of this default is that the Customer may be subject to Article 372 of the Criminal Code regarding embezzlement with a criminal offense imprisonment for a maximum of four years, then Article 36 of Act No. 42 of 1999 concerning Fiduciary Guarantees carries a maximum penalty of 2 years.